A model integration framework for linking SWAT and MODFLOW. (November 2015) - Guzman, J.A.; Moriasi, D.N.; Gowda, P.H.; Steiner, J.L.; Starks, P.J.; Arnold, J.G.; Srinivasan, R.
Abstract: Assessment of long-term anthropogenic impacts on agro-ecosystems requires comprehensive modelling capabilities to simulate water interactions between the surface and groundwater domains. To address this need, a modelling framework, called "SWATmf", was developed to link and integrate the Soil Water Assessment Tool (SWAT), a widely used surface watershed model with the MODFLOW, a groundwater model. The SWATmf is designed to serve as a project manager, builder, and model performance evaluator, and to facilitate dynamic interactions between surface and groundwater domains at the watershed scale, thus providing a platform for simulating surface and groundwater interactions. Using datasets from the Fort Cobb Reservoir experimental watershed (located in Oklahoma, USA), the SWATmf to facilitate linkage and dynamic simulation of SWAT and MODFLOW models. Simulated streamflow and groundwater levels generally agreed with observations trends showing that the SWATmf can be used for simulating surface and groundwater interactions. Highlights: A modelling framework integrating SWAT and MODFLOW models based on structure grids and a unified spatio-temporal frame. Implementation of model capabilities for simulating multiple surface watersheds contributing to single aquifer domain. Simulation of daily groundwater from irrigation needs and distributed percolation fluxes in the watershed. Assessment of linkages between groundwater levels and extracted volumes during the 2011 and 2012 dry period in Oklahoma.